The Modelling and Analysis of iPWR-Type SMR Core Dynamics: Control Rods, Reactivity Feedback, and Thermal-Hydraulic Effects - Septawijaya, G.; Sukarman, S.; Bakhri, S.; Subekti, M. (Atom Indonesia, 2024)
Development plans for Nuclear Power Plants (NPPs) in Indonesia have been widely discussed. One of the planned NPP types is the Small Modular Reactor (SMR). Human resource readiness is an essential aspect to be considered before constructing an NPP. Simulators capable of illustrating core dynamics can be used to educate the public about the processes within a nuclear reactor. Core modeling is a key component in developing an NPP simulator. The neutronic behavior of the reactor core is modeled using point kinetics equations, while the thermal-hydraulic aspect uses Mann’s model. The results indicate that the modeled core can operate up to 160 MWt and other operating parameters at maximum power align well with the SMR reactor design certification data.